EFECTO DEL QUITOSANO SOBRE LA RESPUESTA AGRONÓMICA EN LECHUGA (Lactuca sativa L.) CULTIVADA EN ACUAPONÍA - Ayala Delgado, Joel Alejandro (2023)
Lettuce is one of the most consumed plants worldwide, it has incomparable nutritional properties in relation to other vegetables. The use of chitosan as an ecological alternative in the management of agricultural productions has recently been studied for its high potential in stimulating growth, antiviral, antifungal and antibacterial activity. The research was conducted at the Campus Experimental “La María” de la Universidad Técnica Estatal de Quevedo. With the objective of evaluating the effect of chitosan on the agronomic response in lettuce (Lactuca sativa L.) grown in aquaponics.